Moving in the right direction: tobacco packaging and labeling in the Americas - Eric Crosbie; Olufemi Erinoso; Sara Perez; Ernesto M. Sebrié (Pan American Health Organization, 2022)
Objective. To assess the adoption of tobacco packaging and labeling policies based on the World Health Organization (WHO) Framework Convention on Tobacco Control (FCTC)'s Article 11 guidelines, in the WHO Region of the Americas (AMRO). Methods. We reviewed tobacco control laws in AMRO from the Campaign for Tobacco-Free Kids' Tobacco Control Laws database. We analyzed four sub-policy areas for smoked and smokeless tobacco products: 1) health warning labels (HWLs), 2) constituents and emissions (C&Es), 3) misleading tobacco packaging and labeling, and 4) standardized "plain" packaging. Results. Of 35 countries in AMRO, 31 have tobacco packaging and labeling laws. Twenty-six countries require pictorial HWLs, 24 require warnings printed on at least 50% of the front and back of the packs, and 24 rotate a single or multiple (from 2 to 16) warnings within a specified period (from 5 up to 24 months). Only 21 countries require descriptive messages on toxic C&Es information. Twenty-seven countries ban brand descriptors with references to implied harm reduction (e.g., "light"), 24 ban figures, colors, and other signs, but only 13 prohibit emission yields printed on the packs. Only Canada and Uruguay have adopted standardized tobacco packaging while Uruguay also requires a single presentation (one brand variant) per brand family. Conclusion. Many countries in AMRO have made good progress in adopting multiple, rotating, large pictorial HWLs and banning misleading brand descriptors. However, there needs to be greater attention on other tobacco packaging and labeling provisions with a focus on implementing standardized tobacco packaging.